Functional diversity of afrotropical fish communities across river gradients in the Republic of Congo, west central Africa - Walsh, Gina; Pease, Allison A.; Woodford, Darragh J.; Stiassny, Melanie L.J.; Gaugris, Jérôme Y.; South, Josie (Frontiers in Environmental Science, 2022)
Characterizing functional freshwater biodiversity patterns and understanding community determinants can aid in predicting changes and prioritizing specific conservation management actions. Afrotropical freshwater systems support diverse ecological communities, including many taxonomically undescribed species, yet few studies have been undertaken in this region and they remain poorly understood. Here, we use functional trait-based approaches to describe the functional diversity of fish assemblages in the Republic of Congo (west Central Africa) from the headwaters of a large basin (upper basin) to the coastal plains (lower basin). Functional traits were assessed using multivariate ordination, and functional diversity was calculated using functional trait-space occupation. We investigated if fish β diversity is nested regionally and at a basin-scale to understand if species assemblages exhibit non-random or environmental filtering patterns. Trait-environment relationships were modeled to determine the most significant drivers of trait diversity, and functional richness (FRic) was calculated for communities in both basins to identify whether Afrotropical systems conform to expected patterns of biodiversity along a fluvial gradient. Moderate to weak community nestedness and various traits associated with resistance and feeding were significantly correlated with habitat variables in the upper and lower basins respectively. Whilst environmental filtering is an important process of community assembly at basin scale, non-random processes are evident in the upper basin, whereas a high turnover was noted in the lower basin. Trophic traits in larger coastal plain habitats of the lower basin suggest higher trophic diversity is associated with higher spatial heterogeneity and nutrient concentrations. High functional turnover between headwaters and coastal plains suggests different functional strategies in fish assemblages between localities along the fluvial gradient. In contrast to expectations derived from temperate lotic systems, functional richness was comparable across both basins which suggests that headwater zones in the region harbor substantial functional diversity, especially when considering upstream catchment size. Functional diversity and environment patterns documented show unique patterns of functional richness that may assist in improving understanding of responses, vulnerabilities and conservation needs in Afrotropical systems.